Analisis Proses Perumusan CP: Merdeka Mengajar? Analysis of the CP Formulation Process: Independent Teaching? - Eppendi, Jhoni; Ilham, Muhammad; Vega, Nofvia De (ITScience (Information Technology and Science), 2024)
The transformation of education in Indonesia has become a central issue that continues to be discussed in the realm of national education. The government is trying to present a curriculum that is adaptive and relevant to the needs of the times, one of which is by creating the Merdeka Curriculum. Although the Merdeka Curriculum gives teachers greater authority, there is a lack of comprehensive research on how the conversion from CP to ATP impacts the concept of Merdeka Mengajar. This study aims to analyze the process of formulating CP to ATP with the aim of exploring the meaning of